Intérêt D’une Recherche De Thrombophilie Au Cours Des Thromboses De La Veine Porte Dans Un Service De Médecine Interne - S., Brah; B., Malam-Abdou; M., Daou; A., Andia; A., Djibrilla; V., Veit; E., Bernit; J., Hardwigsen; 1.Schleinitz; J., Harlé (European Scientific Journal, ESJ, 2017)
Background: Many causes of portal vein thrombosis are described and most patients had a combination of local and systemic risk factors. In many studies, prtothombotic disorders investigations were conducted in various departments of haematologies and/or gastroenterology. In this study, we investigated the systemic risk factors associated or not to abdominal inflammation in a series of patients recruited in a department of Internal Medicine. Methods: We studied, retrospectively from 2005 to 2009, 21 cases of patients with portal vein thrombosis. Patients with cancer are not included in this study. Results: We reported 21 patients with portal vein thrombosis: 8 males (43%) and 13 females (57%). The average age of patients was 46, 6 years (20; 59). Eight (8) patients had abdominal inflammatory pathology and 21 (100%) patients had systemic prothrombotic factors. This etiologic investigation is rentable because in 18 cases, abdominal inflammation and/or prothombotic disorders are diagnosed. This diagnostic, however, can permit to discuss a specific management. Conclusion: Extensive investigation of prothrombotic disorders is necessary in portal vein thrombosis, although if local abdominal inflammation exist.